Sovranità contese e cluster. La rinascita dellapace in Libano - Montuoro, Umberto (Rivista di studi politici internazionali, 2007)
The Libanese national State seems to be a non leading actor during the Israeli intervention, the reasons for which can be assessed in several fundamental points. Territorial supremacy and the armed forces; the inadequate level of intelligence does not permit a real discrimination of military objects; the intelligent bombs, the satellites and Humint. The presence of the United Nations is established by the contents of Resolution 1701 regarding the matter of safeguarding sovereign prerogatives. The engagement of UN for the protection of the civilian population starts with the consideration of Explosive War Remnants, cluster bombs and the introduction of development in the area. Some important hypothesis of work came out of the 6th to 15th session of the Geneva conference on disarmament, including Italian action for the plan of codification of humanitarian law. Finally the thrust of development emphasised by the 3rd review conference. The UNIFIL mission in the Libanese mosaic offers specular prospects in that field and becomes an extraordinary political and juridical laboratory. Italy is part of multinational contingent, therefore, in this prospective, the centre of the UN restarts from the European Union. RÉSUMÉ - L’état national libanais parait jouer les ‘seconds rôles’ pendant le conflit. Les raisons de l’intervention israélienne s’articulent en quelques points fondamentaux: a) la souveraineté territoriale et les formations armées; b) le seuil pas adéquat de l’intelligence ne permet pas une réelle discrimination des objectifs militaires; c) les bombes intelligentes ou l’intelligence, les satellites et l’Humint. L’intervention des Nations Unies est établie par les contenus de la Résolution 1701 en matière de sauvegarde des prérogatives souveraines. L’engagement de l’ONU pour la tutelle de la population civile commence par la prise en compte des engins non explosés, bombes cluster et des prémisses de développement de l’aire. À la conférence sur le désarmement de Genève émergent d’importantes hypothèses de travail: de la 6ème à la 15ème session. L’action de l’Italie sur le plan de la codification du droit humanitaire. Pour terminer, la poussée évolutive imposée par la 3ème conférence de révision. La mission UNIFIL dans la mosaïque libanaise offre des perspectives d’application réciproques sur le champ et devient un extraordinaire laboratoire politique et juridique, L’Italie est dans le contingent multinational. Dans cette perspective, la centralité des Nations Unies recommence de l’Union Européenne.